Previous preeclampsia and its association with the future development of cardiovascular diseases: a systematic review and meta-analysis - Veiga, Eduardo Carvalho de Arruda; Rocha, Paulo Ricardo Higassiaraguti; Caviola, Leonardo L.; Cardoso, Viviane Cunha; Costa, Fabricio da Silva; Saraiva, Maria da Conceição Pereira; Barbieri, Marco Antonio; Bettiol, Heloisa; Cavalli, Ricardo Carvalho (Clinics, 2021)
Preeclampsia is a multifactorial disease. Among these factors, untreated hypertension during pregnancy can result in high morbidity and mortality rates and may also be related to the future development of cardiovascular diseases.Therefore, this systematic review aimed to determine the association of previous preeclampsia with the future development of cardiovascular diseases. Studies on the association between preeclampsia and future cardiovascular diseases published in the last 10 years (2009–2019) were identified from the PubMed/Medline (207 articles), Embase (nine articles), and Cochrane (three articles) databases using the keywords ‘‘preeclampsia’’ and ‘‘future cardiovascular diseases’’, ‘‘preeclampsia’’ and ‘‘future heart attack’’, and ‘‘preeclampsia’’ and ‘‘future cardiac disease’’. After applying the inclusion and exclusion criteria, 15 articles were analyzed by systematic review and meta-analysis according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The meta-analysis and the determination of the quality of the articles were conducted using RevMan software, version 5.3. Statistically significant differences were observed between the control and previous preeclampsia groups with respect to systolic blood pressure (mean difference [MD] 4.32; 95% confidence interval [95%CI] 3.65, 4.99; po0.001), diastolic blood pressure (MD: 2.11; 95%CI: 1.68, 2.55; po0.0001), and insulin level (MD: 2.80; 95% CI: 0.50, 5.11; po0.001). Body mass index (MD: 2.57, 95%CI: 2.06, 3.07; p=0.0001), total cholesterol (MD: 10.39; 95% CI: 8.91, 11.87; p=0.0001), HDL (MD: 2.83; 95%CI: 2.20, 3.46; p=0.0001), and LDL (MD: 1.77; 95%CI: 0.42, 3.13; p=0.0001) also differed significantly between groups. Thus, the results of the present study showed that women with a history of preeclampsia were more likely to develop cardiovascular disease.